Dynamic Regulation of RGS2 Suggests a Novel Mechanism in G-Protein Signaling and Neuronal Plasticity - Ingi, Tatsuya (J Neurosci, 1998)
Long-term neuronal plasticity is known to be dependent on rapidde novo synthesis of mRNA and protein, and recent studies provide insight into the molecules involved in this response. Here, we demonstrate that mRNA encoding a member of the regulator of G-protein signaling (RGS) family, RGS2, is rapidly induced in neurons of the hippocampus, cortex, and striatum in response to stimuli that evoke plasticity. Although several members of the RGS family are expressed in brain with discrete neuronal localizations, RGS2 appears unique in that its expression is dynamically responsive to neuronal activity. In biochemical assays, RGS2 stimulates the GTPase activity of the α subunit of G(q) and G(i)1. The effect on G(i)1 was observed only after reconstitution of the protein in phospholipid vesicles containing M2 muscarinic acetylcholine receptors. RGS2 also inhibits both G(q)- and G(i)-dependent responses in transfected cells. These studies suggest a novel mechanism linking neuronal activity and signal transduction.